Cancer‐driven changes link T cell frequency to muscle strength in people with cancer: a pilot study. Issue 4 (12th April 2019) - Narsale, Aditi; Moya, Rosa; Ma, Jasmin; Anderson, Lindsey J.; Wu, Daniel; Garcia, Jose M.; Davies, Joanna D.
Abstract: Background: Tumour growth can promote the loss of muscle mass and function. This is particularly disturbing because overall survival is significantly reduced in people with weaker and smaller skeletal muscle. The risk of cancer is also greater in people who are immune deficient. Muscle wasting in mice with cancer can be inhibited by infusion of CD4 + precursor T cells that restore balanced ratios of naïve, memory, and regulatory T cells. These data are consistent with the hypothesis that stronger anti‐cancer T cell immunity leads to improved muscle mass and function. As a first step to testing this hypothesis, we determined whether levels of circulating T cell subsets correlate with levels of muscle strength in people with cancer. Methods: The frequency of circulating CD4 + and CD8 + naïve, memory, and regulatory T cell subsets was quantified in 11 men with gastrointestinal cancer (aged 59.3 ± 10.1 years) and nine men without cancer (aged 60 ± 13 years), using flow cytometry. T cell marker expression was determined using real‐time PCR and western blot analyses in whole blood and peripheral blood mononuclear cells. Handgrip strength, one‐repetition maximum chest press, and knee extension tests were used to determine muscle strength. Performance was determined using a stair climb test. Body composition was determined using dual‐energy X‐ray absorptiometry scan. The Karnofsky and ECOG scales were used to assess functional impairment. Correlations between frequencies of cell subsets with strength, performance, and body composition were determined using regression analyses. Results: Our data show significant correlations between (i) higher frequencies of CD8 + naïve ( P = 0.02) and effector memory ( P = 0.003) T cells and lower frequencies of CD8 + central memory T cells ( P = 0.002) with stronger handgrip strength, (ii) lower frequency of regulatory cells with greater lean mass index ( P = 0.04), (iii) lower frequency of CD8 + T cells that express CD95 with greater stair climb power ( P = 0.003), (iv) higher frequency of T cells that co‐express CD197 and CD45RA and greater one‐repetition maximum knee extension strength ( P = 0.008), and (iv) higher expression of CD4 in whole blood with greater functional impairment ( P = 0.004) in people with cancer. Conclusions: We have identified significant correlations between levels of T cell populations and muscle strength, performance, and body composition in people with cancer. These data justify a follow‐up study with a larger cohort to test the validity of the findings.